Applying Pause Analysis to Explore Cognitive Processes Occurring During the Copying of Sentences Amongst 6 years old Children in Sekolah Kebangsaan Bandar Tasik Puteri - Putri Afzan Maria Zulkifli; Azhar Md Adnan; Cik Norazlina Mohamad; Mahani Abdul Malik (2014)

(untitled)
Pause analysis is a method that investigates processes of writing by measuring the amount of time between pen strokes. It provides the field of teaching and learning in the 21st century with insights of the cognitive processes underpinning the nature of writing in children. This study examined the potential of using free handwritten copying of sentences as a means of investigating components of the cognitive processes of children who have English as their Second Language (ESL). An experiment is conducted where 28 children of Sekolah Kebangsaan Bandar Tasik Puteri are asked to copy a sentence in Malay Language and a sentence in English. The handwritten activity is captured to study the pause lengths produced at different forms of chunking sizes (i.e. group of words, words and group of letters). Results are then associated to the Theoretical Model of Copying (MoC) in identifying the possible factors that might affect the chunking sizes. It was found that there is a clear chunk with long pauses that occur at letter level, group of letters and word level. This indicates that there is a possibility of language comprehension processes taking place during the copying of sentences.